A comprehensive review of catalyst deactivation and regeneration in heavy oil hydroprocessing - Phuong T.H. Pham; Cham Q. Pham; Thi-Tam Dam; Quang-Anh Nguyen; Tung M. Nguyen (Fuel Processing Technology)
Catalyst deactivation and regeneration are critical aspects of heavy oil hydroprocessing. This review provides a comprehensive overview of the factors contributing to catalyst deactivation, including coke formation, metal and other heteroelement poisoning, and active metal sintering. We delve into the mechanisms underlying these deactivation processes and discuss their impact on catalyst performance and reactor operations. Furthermore, the review explores various catalyst regeneration techniques, such as combustion and gasification techniques. We evaluate the effectiveness of these methods in removing coke and restoring catalyst activity. Additionally, we discuss strategies for mitigating coke formation, including the development of more coke-resistant catalysts and the addition of solvents and surfactants. Refineries can optimize their operations, improve product yields, and minimize environmental impact by understanding the causes of catalyst deactivation and the effectiveness of different regeneration techniques.